ANALISIS DAMPAK PROGRAM PERCEPATAN PENGENTASAN KEMISKINAN (P3K) USAHATANI JAGUNG TERHADAP PENDAPATAN PETANI DI KECAMATAN PALELEH KABUPATEN BUOL PROVINSI SULAWESI TENGAH - Amirudin Rauf; Fathurrahman Fathurrahman; Patta Tope dan Moh; Ahlis Djirimu (Jurnal Akuntansi dan Pajak, 2022)
This study aims to analyze the influence of the Poverty Alleviation Acceleration Program (P3K) on increasing the income of corn farmers in Paleleh District, Buol Regency, Central Sulawesi Province. This type of research is developmental studies, namely research that aims to determine the development of the subject. The data for this study were obtained by respondents from corn farmers in Paleleh District, Buol Regency, Central Sulawesi Province. The hypothesis testing technique uses multiple linear regression analysis. The results of the analysis show that the Poverty Reduction Acceleration Program as measured by the variables of seeds, fertilizers, pesticides, and processing simultaneously has a significant effect on farmers' income from corn farming. The partial test results prove that the variables of seeds, fertilizers, pesticides, and processing have a significant effect on farmers' income from corn farming in Paleleh District, Buol Regency, Central Sulawesi Province. This indicates that optimizing the strategy of providing seeds, fertilizers, pesticides, and their processing can change the quality of corn farmers' harvests which can have an impact on people's desire to buy crops while being able to increase the income of corn farmers in the area, especially in Paleleh District, Buol Regency, Sulawesi Province. Middle.